Interactions between Fibroblasts and Keratinocytes in Morphogenesis of Dermal Epidermal Junction in a Model of Reconstructed Skin - Marionnet, Claire; Pierrard, Cécile; Vioux-Chagnoleau, Corinne; Sok, Juliette; Asselineau, Daniel; Bernerd, Françoise (Journal of investigative dermatology, 2006)
De novo dermal epidermal junction morphogenesis was studied in a skin model including dermal fibroblasts and epidermal keratinocytes. Sequential gene expression, protein deposition, and localization of basement membrane zone components were studied during 15 days. The morphogenesis of dermal epidermal junction is characterized by an implementation of the different components and then a subsequent plateau phase occurring at day 11. Three groups of genes were identified depending on cellular origin and expression profile: 1/genes of fibroblastic origin (col I alpha1, col III alpha1, nidogen, and fibrillin 1); 2/genes expressed in fibroblasts and keratinocytes with symmetrical expression pattern between both cell types (col IV alpha1, col VII alpha1, and tenascin C); 3/laminin beta3 only expressed in keratinocytes. Use of modified organotypic models excluding one cell type revealed a tight interplay between fibroblasts and keratinocytes for synthesis and localization of the components of dermal epidermal junction. Keratinocytes downregulated mRNA and proteins of fibroblastic origin, upregulated col VII in fibroblasts and were absolutely required for dermal–epidermal junction localization of fibroblastic proteins. Fibroblasts downregulated mRNA of keratinocytes and were needed for extracellular secretion and correct localization of type VII collagen and laminin 5.